2011
DOI: 10.3758/s13414-011-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Lightness constancy and illumination discounting

Abstract: Contrary to the implication of the term "lightness constancy", asymmetric lightness matching has never been found to be perfect unless the scene is highly articulated (i.e., contains a number of different reflectances). Also, lightness constancy has been found to vary for different observers, and an effect of instruction (lightness vs. brightness) has been reported. The elusiveness of lightness constancy presents a great challenge to visual science; we revisit these issues in the following experiment, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Gamut relativity is-to cite another example-consistent with recent psychophysical and modeling work supporting the idea that achromatic colors are specified in terms of two perceptual coordinates [61,62]. According to gamut relativity, these coordinates are whiteness and blackness, whereas alternative proposals either assert that these coordinates correspond to brightness and lightness (without specifying the mapping from luminance) [61] or leave the coordinates unspecified altogether [62]. The advantage of gamut relativity, then, is that the theory specifies perceptual coordinates in terms of a specific mapping from luminance values.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Gamut relativity is-to cite another example-consistent with recent psychophysical and modeling work supporting the idea that achromatic colors are specified in terms of two perceptual coordinates [61,62]. According to gamut relativity, these coordinates are whiteness and blackness, whereas alternative proposals either assert that these coordinates correspond to brightness and lightness (without specifying the mapping from luminance) [61] or leave the coordinates unspecified altogether [62]. The advantage of gamut relativity, then, is that the theory specifies perceptual coordinates in terms of a specific mapping from luminance values.…”
Section: Discussionsupporting
confidence: 61%
“…The difference is illustrated in the manner in which gamut relativity explains a wide range of phenomenology in a unified way. The theory explains, for instance, why surface regions with the same diffuse reflectance, seen under different perceived illumination levels, cannot be perceptually matched [61,62]; namely, a given surface lightness layer contains points whose whiteness coordinates differ but nonetheless can be perceptually grouped into layered representations due to their relative proximity in blacknesswhiteness space [54]. The theory also explains how observers can perceive discontinuous whitish highlight and blackish shading layers in Figs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies were all conducted using naive subjects and experimental methods other than adjustment-based asymmetric matching (such as achromatic adjustment or palette matching) and, predominantly, a between-subjects design (Logvinenko & Tokunaga 2011 study was within-subjects). In addition, these studies employed more naturalistic stimulus configurations than the studies reviewed above that reported large instructional effects.…”
mentioning
confidence: 99%
“…It is often reported that lightness judgments are closer to reflectance matches whereas brightness judgments are closer to luminance matches (Arend & Goldstein, 1987;Arend & Reeves, 1986;Arend, Reeves, Schirillo, & Goldstein, 1991;see also Bauml, 1999;Cornelissen & Brenner, 1995;Troost & de Weert, 1991). However, subsequent work has shown that the size of these instructional effects (or whether there is an effect of instructions) depends on the class of stimuli (simple versus complex/ natural scenes), the task (asymmetric matching, achromatic adjustment, palette matching, or color selection task; Delahunt & Brainard, 2004;Logvinenko & Tokunaga, 2011;Madigan & Brainard, 2014;Ripamonti et al, 2004), and whether a within-or betweensubjects design was implemented (for further discussion, see Radonjić & Brainard, 2016). In our study, all stimuli were rendered under the same illumination, so reflectance and intensity matches would have been identical.…”
Section: Possible Explanations For Matching Behaviormentioning
confidence: 99%